The Indonesian MSME Compass: Navigating Sustainable Performance with Innovation, Dynamic Capabilities, and Green Entrepreneurial Mindset - Angeline, Monica; Andrian, Tommy (International Journal of Economics and Financial Issues, 2025)
This study investigates the role of innovation (INV), dynamic capabilities (DCS), and green entrepreneurial orientation (GEO) in enhancing the sustainability performance of micro, small, and medium enterprises (MSMEs) in Indonesia. The study uses quantitative methods, with primary data using questionnaire through google form with a total of 162 respondents consisted of owners, directors, managers, and supervisors from MSMEs in Jakarta and Tangerang area (Indonesia). Data processed using SPSS and Smart PLS as a stastistical tool. The study finds that innovation, dynamic capabilities, and green entrepreneurial orientation significantly influence sustainability performance. Based on these insights, this study recommends that MSMEs should prioritize on strengthening team dynamic capabilities to foster resilience, enhancing innovation to improve competitiveness, and integrating green entrepreneurial orientation into strategic practices. Collectively, these efforts can substantially improve sustainability performance across economic, environmental, and social dimensions. By focusing on sustainability performance, MSMEs play a pivotal role in reducing income disparities and supporting national economic growth, thereby directly contributing directly to the realization of the United Nations Sustainable Development Goals, particularly SDG 8 on Decent Work and Economic Growth.